Self-organizing neuro-fuzzy control of complex systems - Fabro, Toao; Gomide, Fernando (Zielona Góra: Uniwersytet Zielonogórski)
An autonomous system control creates a need for classes of control systems whose behaviour should emerge as a consequence of its interaction with the environment. Autonomous systems must be able to adapt continuously to new and unpredictable situations and to be successful in accomplishing their tasks. In this paper, a self-organizing, neuro-fuzzy control architecture for complex systems is presented.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka